Combined treatment with epigenetic agents enhances anti-tumor activity of MAGE-D4 peptide-specific T cells by upregulating the MAGE-D4 expression in glioma - Bi, Shui-Qing; Zhang, Qing-Mei; Zeng, Xia; Liu, Chang; Nong, Wei-Xia; Xie, Huan; Li, Feng; Lin, Li-Na; Luo, Bin; Ge, Ying-Ying; Xie, Xiao-Xun (Frontiers in Oncology, 2022)
Objective: To evaluate the efficacy of combined epigenetic drugs of decitabine (DAC), valproic acid (VPA), and trichostatin A (TSA) on immunotherapy against glioma. Methods: The expression and prognosis of MAGE-D4 in glioma were analyzed online, and the expression of MAGE-D4 and HLA-A2 in glioma induced by epigenetic drugs was detected by qRT-PCR, Western blot, and flow cytometry. Methylation status of the MAGE-D4 promoter was determined by pyrosequencing. HLA-A2 restricted MAGE-D4 peptides were predicted and synthesized, affinity assay and peptide/HLA complex stability assay were performed to determine the affinity between peptide and HLA. CCK8 assay, CFSE assay, ELISA and ELISPOT were performed to detect the function of MAGE-D4 peptide-specific T cells. Flow cytometry, ELISA, and cytotoxicity assays were used to detect the cytotoxicity effect of MAGE-D4 peptide-specific T cells combined with epigenetic drugs against glioma in vitro. Finally, the glioma-loaded mice model was applied to test the inhibitory effect of specific T cells on gliomas in vivo. Results: MAGE-D4 was highly expressed in glioma and correlated with poor prognosis. Epigenetic drugs could induce the expression of MAGE-D4 and HLA-A2 in glioma. MAGE-D4-associated peptides were found that induce DCs to stimulate the highest T cell activities of proliferation, IL-2 excretion, and IFN-γ secretion. MAGE-D4 peptide-specific T cells had the most cytotoxicity effectivity on glioma treated with TSA only or combining TSA and DAC, and its cytotoxicity effect on glioma cells decreased significantly after HLA blocking. In vivo experiments also confirmed that MAGE-D4 specific T cell has an inhibitory effect on TSA-treated glioma. Conclusion: MAGE-D4 is highly expressed in glioma and correlated with the prognosis of glioma. A novel MAGE-D4 peptide identified was capable to induce MAGE-D4-specific T cells that can effectively inhibit glioma growth, and the epigenetic drug application can enhance this inhibition.